Effect of lactobacilli on E. coli adhesion to Caco-2 cells in vitro - Horosová, K; Bujnáková, D; Kmet, V (Folia microbiologica, 2006)
Inhibitory effect of various lactobacilli against pathogenic strains of E. coli in model system Caco2 cells was determined by enumerating the number of adhering E. coli after pre-incubation (exclusion), post-incubation (displacement) or co-incubation (competition) with lactobacilli. Porcine E. coli strain F107 (F18ab, Stx2v) in the competition assay with porcine lactobacillus strain P10 gave bacterial counts 7.25 (log CFU per well); in the exclusion test it was only 7.05 while in displacement test it reached 7.29. The lowest E. coli counts adhering to Caco-2 cells were in exclusion assay (pre-incubation, Lactobacillus inoculated as the first). Pre-treatment of E. coli with our lactobacilli strains reduced the cultivable E. coli numbers.
Keywords: Lactobacillus; prasata; Caco-2 buňky; Bacterial Adhesion; Probiotics; Swine; počet mikrobiálních kolonií; střevní sliznice; Animals; bakteriální adheze; lidé; Colony Count, Microbial; Escherichia coli; Humans; Caco-2 Cells; zvířata; Intestinal Mucosa; probiotika